Mesa Redonda: “Analizando el Código de Consumo” - Falla Jara, Alejandro; Tovar Mena, Teresa; Gagliuffi Piercechi, Ivo; Lesem Guerra, Eliana (Revista de Derecho Administrativo, 2011)
El artículo no presenta resumen.